Lipid mediators in post-mortem brain samples from patients with Alzheimer's disease: A systematic review - Aidan D. Tyrrell; Giulia Cisbani; Mackenzie E. Smith; Chuck T. Chen; Yue-Tong Chen; Raphael Chouinard-Watkins; Kathryn E. Hopperton; Ameer Y. Taha; Richard P. Bazinet (Brain, Behavior, & Immunity - Health)
A proposed contributor to Alzheimer's disease (AD) pathology is the induction of neuroinflammation due to tau and beta-amyloid protein accumulation causing neuronal injury and dysfunction. Dysregulation of lipid mediators derived from polyunsaturated fatty acids may contribute to this inflammatory response in the brain of patients with AD, yet the literature has not yet been systematically reviewed. A systematic search was conducted in Medline, Embase and PsychINFO for articles published up to April 22, 2024. Papers were included if they measured levels of lipid mediators and/or enzymes involved in their production in post-mortem brain samples from patients with AD and control without neurological disease. A total of 50 relevant studies were identified. Despite heterogeneity in the results, pro-inflammatory lipid mediators, including 5-, 11-, 12- and 15-hydroxyeicosatetraenoic acid oxylipins and prostaglandin D2, were significantly higher, while anti-inflammatory lipoxin A4 and DHA-derived docosanoids were significantly lower in brains of patients with AD compared to control (16 studies). Thirty-seven articles reported on enzymes, with 32 reporting values for enzyme level changes between AD and controls. Among the 32 articles, the majority reported on levels of cyclooxygenase (COX) (18/32), with fewer studies reporting on phospholipase (8/32), lipoxygenase (LOX) (4/32) and prostaglandin E synthase (4/32). Enzyme levels also exhibited variability in the literature, with a trend towards elevated expression of enzymes involved in the pro-inflammatory response, including COX and LOX enzymes. Overall, these results are consistent with the involvement of neuroinflammation in the pathogenesis of AD measured by lipid mediators. However, the specific contribution of each lipid metabolite and enzymes to either the progression or persistence of AD remains unclear, and more research is required.